ChemInform Abstract: Palladium(II)‐Catalyzed Synthesis of 2H, 3′H‐Spiro[benzofuran‐3, 2′‐naphthoquinones]. Issue 5 (4th February 2014) - Claes, Pieter; Jacobs, Jan; Kesteleyn, Bart; Nguyen Van, Tuyen; De Kimpe, Norbert
Abstract Novel spiroheterocycles are prepared by an unprecedented Pd‐catalyzed spirocyclization.